Potential risk of HIV transmission in barbering practice among professional barbers in Ibadan, Nigeria (2009)
Background: There is a growing concern that barbering procedures could create opportunities for HIV transmission. However, little is known about Nigerian barbers' practices relating to the prevention of HIV. Objectives: This study assessed the precautionary measures for the prevention of HIV among commercial barbers in Ibadan, Nigeria. Methods: Data were collected using validated checklist to directly observe ninety barbering procedures in forty-five barber shops randomly selected from three communities that have been categorized as inner-core, transitory and peripheral. Results: Respondents were all males with mean age of 36(±10.2) years. Ninety-eight percent had at least primary school education and all of them learnt barbering through apprenticeship. The instruments used were razor blades (11.1%), manual clippers (8.9%) and electric clippers (80%). Clippers were sterilized in 10% and disinfected in 72.5%, while no decontamination was carried out in 17.5% of the sessions. Fifty two percent of the disinfections involved the use of kerosene, a disinfectant not recommended for HIV inactivation; 48 .3% of the disinfectants were not in the original containers while 53.4% of the sessions involved the use of same brush for cleaning clipper and brushing hair. Hand-held flame and Ultra-violet light sterilizer were used in 50% of the sterilization process. Barbers in the high-class peripheral communities were more likely to practice appropriate equipment decontamination than those from lower-class inner-core communities. There was blade-to-skin contact in all and accidental cuts occurred in three of the sessions and none was properly managed. Conclusion: The risk of transmitting HIV is high in the barbershops in the study area. Health education strategies such as training, supportive supervision and peer education are needed to facilitate the adoption of effective precautionary measures against HIV infection among barbers.